Wage setting and wage flexibility in Ireland - Results from a firm-level survey - Mary Keeney; Martina Lawless (European Central Bank (ECB), 2010)
This paper investigates the wage-setting behaviour of Irish firms. We place particular emphasis on the use of flexible pay components and examine how these allow firms to deal with shocks requiring a reduction in costs without having to cut base wages. The results presented in this paper are based on a survey of Irish firms undertaken as part of the Wage Dynamics Network (WDN), which is a Euro-system research network. Our main findings are that almost two-thirds of firms applied at least some elements of the national wage agreement in place at the time of the survey (Towards 2016). Wage cuts or freezes were reported by a very small percentage of firms but changes in bonuses and other flexible pay components were relatively common if the firm needed to reduce labour costs. When asked about the relevance of different explanations for avoiding cuts in base wages, worker morale and loss of experienced workers were the main concerns. Regulatory or collective bargaining obstacles to wage cuts were the lowest ranked.
Keywords: J3; E24; J4; 330; Ireland; survey; Wage Negotiations; Vergütungssystem; Lohnbildung; Lohnrigidität; Leistungsentgelt; Irland